Apprentice In Death - Robb, J.D. 1950- (New York : Berkley, 2016)
"Lieutenant Eve Dallas returns in a fast-paced new novel from #1 New York Times bestselling author J. D. Robb. Nature versus nurture... The shots came quickly, silently, and with deadly accuracy. Within seconds, three people were dead at Central Park's ice skating rink. The victims: a talented young skater, a doctor, and a teacher. As random as random can be. Eve Dallas has seen a lot of killers during her time with the NYPSD, but never one like this. After reviewing security videos, it becomes clear that the victims were killed by a sniper firing a tactical laser rifle, who could have been miles away when the trigger was pulled. And though the locations where the shooter could have set up seem endless, the list of people with that particular skill set is finite: police, military, professional killer. Eve's husband, Roarke, has unlimited resources--and genius--at his disposal. And when his computer program leads Eve to the location of the sniper, she learns a shocking fact: There were two--one older, one younger. Someone is being trained by an expert in the science of killing, and they have an agenda. Central Park was just a warm-up. And as another sniper attack shakes the city to its core, Eve realizes that though we're all shaped by the people around us, there are those who are just born evil.."--
Publishers Weekly
Kirkus Reviews
Booklist
Publishers Weekly Starred Reviews
Adult.
Adult.
Keywords: Police -- Fiction; Women detectives -- Fiction